2021
DOI: 10.51474/jer.v11i1.502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Governance on Educational Performance in Nepal

Abstract: Good governance often seems to have accelerated educational performance. Stepping onto the contribution of governance to the education, this paper examines the effect of Worldwide Governance Indicators produced by Kaufmann et al. (1999) on Educational Performance (EP) of Nepal during the years from 1996 to 2018. The six indicators of WGIs: political stability and absence of violence, government effectiveness, voice and accountability, regulatory quality, control of corruption and rule of law are used as indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Zaman (2016), Ahmad and Saleem (2014), Han et al (2014), and Canfield (2011) have revealed the positive, predictive, and significant relation between worldwide governance indicators and different dependent variables such as economic growth, human development, domestic product, educational outcomes or country growth (Khadka, 2021). However, some other researchers found some dimensions of WGIs that negatively correlate to educational outcomes and others such as government effectiveness with GDP in South Asian countries.…”
Section: Empirical Reviews and Conceptual Frameworkmentioning
confidence: 99%
“…Zaman (2016), Ahmad and Saleem (2014), Han et al (2014), and Canfield (2011) have revealed the positive, predictive, and significant relation between worldwide governance indicators and different dependent variables such as economic growth, human development, domestic product, educational outcomes or country growth (Khadka, 2021). However, some other researchers found some dimensions of WGIs that negatively correlate to educational outcomes and others such as government effectiveness with GDP in South Asian countries.…”
Section: Empirical Reviews and Conceptual Frameworkmentioning
confidence: 99%
“…It can be argued that the index incorporates other measures of education development, such as education expenditure, education personnel, vocational education development, and so on, by including the mean of years of schooling for adults aged 25 years and older and the expected years of schooling for children of school-entering age in the index. Previous studies have widely used this index to capture differences in countries' levels of education development and their subsequent evolution over time (Bryant and Javalgi 2016;Abubakar et al 2018;Khadka 2021).…”
Section: Data and Data Sourcesmentioning
confidence: 99%
“…Their meaningful participation in the community development process could be viewed as 'breaking the silence' which exists as women's culture of silence (Freire, 2005) in patriarchal societies. Their participation ensures their voice at public forums and makes social institutions accountable (Khadka, 2021). The initiation of gender-inclusive governance helps to achieve Goal 5 of the Sustainable development Goals, which is "achieve gender equality and empower all women and girls" (United Nations, 2021, p. 36).…”
Section: Participatory Development Practicesmentioning
confidence: 99%